Body condition scoring: A management tool - Shirley, John E. (Kansas Agricultural Experiment Station, 2011)
Body condition scoring provides a tool to help the dairy herd manager evaluate his/her nutrition and management program. It takes time, has an associated cost, and will result in a positive economic return if one makes management changes suggested by the results. Body condition scoring done simultaneously with other herd events reduces the time required and provides the herd manager with coordinated information.
Keywords: Dairy; Body condition score; Management tool; Dairy cattle